ANALISIS TINGKAT KEPUASAN PENGGUNA JASA LAYANAN ASRAMA MAHASISWA X - Howard S. Giam; Fahrul Riza (Universitas Bunda Mulia, 2017)
The measurement of consumer’s satisfaction level can be assigned by comparing the important level of factor with the satisfaction of the attribute. The aim of this study to compare the important and satisfaction of attribute from the tenant’s dormitory X. Population of this study are the students who become a tenant of dormitory. Samples of 105 tenants were choosen by non probability sampling technique. Result showed that primary factor in evaluating the service quality are maintain cleanliness at the public space (q1), tables and chairs neatly organized at the public space (q2) and the capability of building management staff keep the good atmosphere for rest and study. These three factor as a primary considerations and being attraction for the tenants.Keywords: Service Quality, Consumer Satisfaction, Importance Factors